2006
DOI: 10.1186/1478-4491-4-20
|View full text |Cite
|
Sign up to set email alerts
|

The importance of human resources management in health care: a global context

Abstract: BackgroundThis paper addresses the health care system from a global perspective and the importance of human resources management (HRM) in improving overall patient health outcomes and delivery of health care services.MethodsWe explored the published literature and collected data through secondary sources.ResultsVarious key success factors emerge that clearly affect health care practices and human resources management. This paper will reveal how human resources management is essential to any health care system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
271
0
10

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(282 citation statements)
references
References 7 publications
1
271
0
10
Order By: Relevance
“…In this study, the other health services including labor and delivery were given first priority over postnatal care. Consequently, postnatal units received less attention which included human and material resource allocation.Another study by Kabene, et al, [14] reported that increased staff work overload led to low quality and productivity of health services, increased waiting times and use of personnel without required skills to perform critical interventions.…”
Section: Structural Quality Attributesmentioning
confidence: 99%
“…In this study, the other health services including labor and delivery were given first priority over postnatal care. Consequently, postnatal units received less attention which included human and material resource allocation.Another study by Kabene, et al, [14] reported that increased staff work overload led to low quality and productivity of health services, increased waiting times and use of personnel without required skills to perform critical interventions.…”
Section: Structural Quality Attributesmentioning
confidence: 99%
“…Human for an organization is considering today as the most valuable asset so an organization should be properly administered him [4]. When employees feel inequality regarding pay difference between their profession and other profession then they got dissatisfied and disappointed with their own profession because their retention based on pay structure or compensation.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Keywords: Interprofessional education; Health sciences; Competencies; Technology Introduction A broad base of recent work has provided new models for exploring the complexity of factors leading to the ineffective articulation of healthcare services [1][2][3][4][5][6]. Worldwide, healthcare services could be improved by providing interprofessional, collaborative, patient-centred care that improves patient outcomes while reducing healthcare costs [7][8][9][10][11][12][13][14].…”
Section: Findings and Conclusionmentioning
confidence: 99%
“…The competency matrix was then used as a learning map to define learning resources related to interprofessional education and learning activities associated with such resources to help students develop competencies in interprofessional healthcare planning and delivery. Interactive, computer-based clinical simulations were then developed to portray opportunities in which the learning resources and activities could be explored and to provide more realistic exposure to complexities in healthcare planning and delivery.Keywords: Interprofessional education; Health sciences; Competencies; Technology Introduction A broad base of recent work has provided new models for exploring the complexity of factors leading to the ineffective articulation of healthcare services [1][2][3][4][5][6]. Worldwide, healthcare services could be improved by providing interprofessional, collaborative, patient-centred care that improves patient outcomes while reducing healthcare costs [7][8][9][10][11][12][13][14].…”
mentioning
confidence: 99%